PROSPEK TEKNOLOGI REMEDIASI LAHAN KRITIS DENGAN ASAM HUMAT (Humic Acid) - Suwahyono, Untung (Jurnal Teknologi Lingkungan, 2011)
The green revolution in the 19th century, has met expectations in an effort to increase the productivity of food supply, in the world at least in Indonesia. In the course of time the green revolution movement has given the systemic impact not only on the degradation of ecosystems, but also the productivity of land, especially paddy fields due to the use of agrochemicals that have been over threshold. The impact on soil in Indonesia become ill, there is a change of soil structure, become poorer and finally lost as the land carrying capacity of production. Systemic Degradation covering 18 000 ha of wetland, contamination levels of heavy metals such as Hg, Fe, Cd, Cu has been on conditions that endanger human health also pesticide has an impact resistance to pests.Recovery efforts of agricultural land, will take time, and cost is not cheap. Various studies have been done, to remediation land by using acid-humic substances, and gives results quite encouraging, because it’s quite effective, efficient and inexpensive, compared with conventional methods is to provide an organic material such as kompost.